Extraction of Antioxidants from Winemaking Byproducts: Effect of the Solvent on Phenolic Composition, Antioxidant and Anti-Cholinesterase Activities, and Electrochemical Behaviour - María José Jara-Palacios; Sandra Gonçalves; Francisco J. Heredia; Dolores Hernanz; Anabela Romano (MDPI AG, 2020)
Extraction solvent is a very important factor in the recovery of antioxidants from natural matrices. In this study, the effect of three solvents (ethanol, ethanol/water and water) on the phenolic composition, antioxidant and anti-cholinesterase activities and electrochemical behaviour of four winemaking byproducts (seeds, skins, stems, and pomace) was evaluated. Phenolic composition was determined by the Folin-Ciocalteu method and ultra-high-performance liquid chromatography (UHPLC), antioxidant activity by the capacity to scavenge 2,2-diphenyl-1-picrylhydrazyl and hydroxyl radicals, anti-cholinesterase activity by the Ellman's method, and electrochemical behaviour by cyclic voltammetry. Eight phenolic compounds were quantified with higher content in water/ethanol extracts (e.g., epicatechin in pomace: 17 mg/100 g vs. 7 and 6 mg/100 g in ethanol and water extracts, respectively), although there were some exceptions (e.g., gallic acid in seeds was most abundant in water extracts). Moreover, the highest total phenolic content (TPC) and antioxidant activity were found in ethanol/water extracts (between 2 and 30-fold the values of the other extracts). Overall, the most active extracts in inhibiting both acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) enzymes were ethanol/water and ethanol extracts from seeds (between 31.11 and 53.90%). The electrochemical behaviour allowed for differentiating the extracts depending on the solvent and the byproduct. Our findings indicate that winemaking byproducts represent a source of phenolic compounds with antioxidant and anti-cholinesterase activities and suggest that cyclic voltammetry is a promising technique to evaluate the phenolic extraction process from these byproducts.